Study of some epidemiological aspects of seizure disorders among children in rural area of a district - Potdar, Pralhad Sureshrao (International Journal Of Community Medicine And Public Health, 2018)
Background: Seizures are the most common paediatric neurologic disorder, with 4% to 10% of children suffering at least one seizure in the first 16 years of life. Most seizures occur before age 3 years. Methods: The present study was undertaken with an objective to study prevalence of seizure disorders among the children aged 14 years and below in rural area of a district and to study some socio-demographic factors and some risk factors associated with it among the study subjects. This was a community based cross-sectional descriptive study. Results: The prevalence of seizure disorder in the area studied was 10.84%. Of the total 1200 subjects examined, 52.67% were males and 47.33% were females. Mean age of the study population was 6.48±3.33 years, median was 6 years. Age, sex, family history, and socio-economic status were highly statistically significant with risk of seizure disorders (p<0.01). H/o Head injury, H/o CNS infection were statistically age, sex, family history of seizure disorders and socio-economic status were independently associated with risk of seizure disorders (p<0.01). Conclusions: prevalence of seizure disorder in the area studied was 10.84%.Significant association was observed between seizure disorder and age, sex, socio economic status, family history of seizure disorder, h/o infections and h/o head injury. Further research is needed to better understand the intricate relationship among socio-demographic risk factors and seizure disorders in order to ensure the best possible outcomes for individuals with seizure disorders.